مشكلات قراءة اللغة العربية لغير ناطقين بها وسبيل ازالتها - Nurfin Sihotang (IAIN Padangsidimpuan, 2019)
This is paper explain the problem reading text in arabic for who is not Arabic his mother tongue, the arabic text as another language onsists from the vocal, morphen, syntax and semantic, bi side of that language need skill listening, speaking, writing and reading, all of this have related to each other The problem of reading in arabic text a special for who not arabic his mother tongue, back to the tructur of arabic language from the problem reading vocal, reading morphen and reanding semantic To the solve of that reading prolem in arabic test the student must know and understoot the correct speling of arabic from the vocal, morphen, syntax and semantics and the student and teacher must readyto learnd step by step and to repeat of the lesson reading